Barriers to efficient electrical appliances in Sri Lanka - Sandasiri, T. N.; Shrestha, Ram M.; Fujiwara, Okitsugu; Pacudan, Romeo B.; Swedish International Development Agency (SIDA) (Bangkok : Asian Institute of Technology, 1997)
This study analyses barriers to the adoption of Efficient Electrical Appliances (EEAs) in residential and commercial sectors. Statistical analysis is carried out to identify the statistically significant barriers to the adoption of Energy Efficient Lighting Technologies (EELT). A study to rank the barriers is carried out following the Analytic Hierarchy Process (AHP). Imperfect information, lack of cognitive skill, risk and uncertainty are found to be the significant consumer level barriers to the adoption Energy Efficient Lamps (EELs) in residential sector but not in the commercial sector. Imperfection in capital market is found to be the significant end user level barrier in the commercial sector. High import tax, lack of information campaigns, electricity pricing policies, low price of electricity, high cost of capital, unavailability in the market and lack of performance standards are found to be the macro level barriers to the adoption of EELs. At the partical appliance level, high initial cost, total unawareness, unaffordability are (in descending order) the three most important specific barriers to adoption of Compact fluorescent lamps. Total unawareness, high initial cost, lack of performance standards are the three most important specific barriers (in descending order) in the case of fluorescent lamps.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Electric apparatus and appliances -- Sri Lanka